Behavioral and cognitive drivers of green entrepreneurship in Net Zero context: an empirical analysis from Vietnam - Thao, Ngo Thi Phuong; Truong, Dinh Duc; Lan, Bui Thi Hoang; Quang, Bui Huy; Tam, Duong Duc; An, Nguyen Dong (Frontiers in Climate, 2025)
Entrepreneurship plays a crucial role in socio-economic development, particularly in the context of green and sustainable business practices. This study explores the factors influencing and mediating green entrepreneurial intention (GEI) in Vietnam within the Net Zero context. The research integrates the theory of planned behavior (TPB) and social cognitive theory (SCT) to develop a comprehensive research model. Primary data were collected through a face-to-face survey with 400 business students. The data were analyzed using descriptive statistics, Cronbach's alpha analysis, exploratory factor analysis (EFA), and structural equation modeling (SEM). The results reveal that nine factors directly influence GEI, namely, self-efficacy (SE), attitude toward entrepreneurship, SN, perceived behavioral control, green industry awareness, entrepreneurship education, social persuasion, capital sources, and personality traits. In addition, the study highlights the mediating role of SE in linking the variables of TPB and SCT to GEI. The findings provide practical recommendations for policymakers and educational institutions to promote green entrepreneurship through targeted education, financial support, and enhanced social networks.